A case of early rheumatoid arthritis with rapid bilateral destruction of the hip joints. Issue 1 (2nd January 2018) - Kamiya, Masato; Soen, Satoshi; Ueno, Mitsuo; Yamazaki, Kenji; Murakami, Teppei
Abstract: We report a case of a postmenopausal female patient who first developed rheumatoid arthritis (RA) in the right shoulder joint with subsequent rapid bilateral destruction of the hip joints. She had been prescribed oral non-steroidal anti-inflammatory drugs at a peripheral clinic and had experienced some pain relief. However, she subsequently developed bilateral destruction of the hip joints, which progressed rapidly during the next 6–12 months, for which she had to undergo bilateral total hip arthroplasty. RA rarely occurs in the hip joints in the early stage of the disease, but when it does, the process of joint destruction may progress rapidly. Therefore, with a history of pain in the hip joints in the absence of inducing factors, it is important to initiate the administration of disease-modifying anti-rheumatic drugs along with repetitive radiographic observation.